Comparative performance of modular with cascaded H-bridge three level inverters - Nada Mohamed El-Naggar; Mohamed Adel Esmaeel; Salama Abu-Zaid (Institute of Advanced Engineering and Science, 2023)
The conventional two-level inverter becomes no longer has the ability to cope with the high-power requirement, so this paper discusses two very common topologies of multilevel inverter like modular multi-level converter (MMC) and cascaded H-bridge (CHB) multi-level inverter for induction motor drive applications. This work attempts to investigate the comparison between MMC and CHB. The comparison is done in aspects of the configuration, concept of operation, advantages and disadvantages, the comparison is also consider output voltage (line to line) waveform, total harmonic distortion (THD) of the output line voltage waveform and the current drawn by both inverters. The performance of the inverters under carrier-based pulse width modulation (PWM) technique and mainly in-phase disposition (IPD), level shifted pulse width modulation is viewed. The paper discusses the comparison between the two multilevel inverters (MLIs) with motor drive applications especially induction motor. The operation of the motor is studied under certain value of load torque. The simulation results for the induction motor with the two inverters (modular multi-level and Cascaded H-bride) for three numbers of levels using MATLAB/Simulink are provided). The obtained results are encouraging and promising especially in the improvement of the THD% results.